2011
DOI: 10.1021/es1031097
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Effects of Humic and Fulvic Acids on Quantum Dot Nanoparticles Using Capillary Electrophoresis with Laser-Induced Fluorescence Detection

Abstract: The increasing production and use of quantum dot (QD) nanoparticles have caused concerns on the possibility of contaminating the aquatic and terrestrial ecosystems with wastes that may contain QDs. Therefore, studies on the behavior of QDs upon interaction with components of the natural environment have become of interest. This study investigated the fluorescence and electrophoretic mobility of carboxylic or amine polyethylene glycol (PEG)-functionalized CdSe/ZnS QDs in the presence of two aquatic humic substa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…In relation to nanomaterial characterisation, electrophoresis has been shown to be able to separate nanomaterial of different, size, shape and compositions (Keeney et al, 2009;Lin et al, 2007;Muralidharan et al, 2007). In particular, CE has been used to separate (for example): carbon nanotubes (Pauwels & Van Schepdael, 2012), gold (Liu et al, 2011), iron oxide (Baharifar et al, 2014), silica (Vanifatova et al, 2011), quantum dots (Celiz et al, 2011;Oszwaldowski et al, 2012), polystyrene (Liu et al, 2012b), core shell particles (Vanifatova et al, 2010) and others (Abdel-Haq & Bossù, 2012).…”
Section: Capillary Zone Electrophoresismentioning
confidence: 99%
“…In relation to nanomaterial characterisation, electrophoresis has been shown to be able to separate nanomaterial of different, size, shape and compositions (Keeney et al, 2009;Lin et al, 2007;Muralidharan et al, 2007). In particular, CE has been used to separate (for example): carbon nanotubes (Pauwels & Van Schepdael, 2012), gold (Liu et al, 2011), iron oxide (Baharifar et al, 2014), silica (Vanifatova et al, 2011), quantum dots (Celiz et al, 2011;Oszwaldowski et al, 2012), polystyrene (Liu et al, 2012b), core shell particles (Vanifatova et al, 2010) and others (Abdel-Haq & Bossù, 2012).…”
Section: Capillary Zone Electrophoresismentioning
confidence: 99%
“…To follow quantitative information of free zinc or cadmium ICP‐MS in combination with CE‐LIF was used. Data obtained from research showed that there is no degradation of QDs in the environment, but they do not exclude influence of sunlight and other environment parameters which have not been considered here .…”
Section: Detection Modification Using Qdsmentioning
confidence: 92%
“…CE has proven to be an excellent approach for the separation of a range of ENMs as long as they are in a charged state in solution (e.g. Liu et al, 2005;Schnabel et al, 1997) and is a promising technique for environmental studies (Celiz et al, 2011;Zanker and Schierz, 2012). Despite the limited development of CE for the analysis of ENMs in nanowaste, the use of this technique for routine analysis of waste samples has been demonstrated.…”
Section: Separation Techniquesmentioning
confidence: 99%